2003
DOI: 10.1302/0301-620x.85b5.13587
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered cartilage and bone using stem cells from human infrapatellar fat pads

Abstract: ultipotential processed lipoaspirate (PLA) cells extracted from five human infrapatellar fat pads and embedded into fibrin glue nodules, were induced into the chondrogenic phenotype using chondrogenic media. The remaining cells were placed in osteogenic media and were transfected with an adenovirus carrying the cDNA for bone morphogenetic protein-2 (BMP-2). We evaluated the tissue-engineered cartilage and bone using in vitro techniques and by placing cells into the hind legs of five severe combined immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(207 citation statements)
references
References 26 publications
3
199
1
4
Order By: Relevance
“…MSCs derived from non-cartilaginous knee joint tissues such as the infrapatellar fat pad (IFP) (Dragoo et al 2003;English et al 2007;Jurgens et al 2009;Buckley et al 2010a; Buckley et al 2010b) and synovium (Sakaguchi et al 2005;Yokoyama et al 2005; Mochizuki et al 2006;Pei et al 2008;Pei et al 2009;Sampat et al 2011) have been shown to possess significant chondrogenic potential. One of the key challenges in cartilage tissue engineering is ensuring sufficient functionality of the construct to be implanted which is capable of withstanding the challenging mechanical environment of the joint.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs derived from non-cartilaginous knee joint tissues such as the infrapatellar fat pad (IFP) (Dragoo et al 2003;English et al 2007;Jurgens et al 2009;Buckley et al 2010a; Buckley et al 2010b) and synovium (Sakaguchi et al 2005;Yokoyama et al 2005; Mochizuki et al 2006;Pei et al 2008;Pei et al 2009;Sampat et al 2011) have been shown to possess significant chondrogenic potential. One of the key challenges in cartilage tissue engineering is ensuring sufficient functionality of the construct to be implanted which is capable of withstanding the challenging mechanical environment of the joint.…”
Section: Introductionmentioning
confidence: 99%
“…This further supported the multipotent potential of CFU-Fs. Similar cells have been isolated from different mesenchymal tissues, including synovia (De Bari et al, 2003), tendons (Salingcarnboriboon et al, 2003), skeletal muscles (Bosch et al, 2000) and adipose tissue (Zuk et al, 2001Erickson et al, 2002), including the fat pad of the knee joint (Dragoo et al, 2003). These MSCs were also found in peripheral blood (Kuznetsov et al, 2001); however, their frequency is probably extremely low or variable (Zvaifler et al, 2000) and they are characterized by different cell surface markers (Table 1).…”
Section: Bone Marrow-derived Stromal Stem Cellsmentioning
confidence: 82%
“…This system is referred to as 'micromass pellet culture' or 'aggregate culture'. Constructs are generated by centrifugation of cell suspensions (Johnstone et al, 1998) or by culturing high-density cell droplets (Dragoo et al, 2003). The formation of micromass pellets is based on cell condensation (mediated by N-cadherin) (Hellingman et al, 2010), which represents the onset of chondrogenic differentiation Tuan, 2002a, 2002b;Denker et al, 1999).…”
Section: D Cultivation Of Cellsmentioning
confidence: 99%
“…The formation of micromass pellets is based on cell condensation (mediated by N-cadherin) (Hellingman et al, 2010), which represents the onset of chondrogenic differentiation Tuan, 2002a, 2002b;Denker et al, 1999). Because it is an easy and effective way to study chondrogenesis, this system is frequently used for in vitro cartilage tissue-engineering approaches De Ugarte et al, 2003;Dragoo et al, 2003;Hildner et al, 2010a;Malladi et al, 2006;Mochizuki et al, 2006;Zheng et al, 2006;Zuk et al, 2002).…”
Section: D Cultivation Of Cellsmentioning
confidence: 99%
See 1 more Smart Citation